A unified model of the excitability of mouse sensory and motor axons. Issue 3 (15th July 2018) - Makker, Preet G. S.; Matamala, José M.; Park, Susanna B.; Lees, Justin G.; Kiernan, Matthew C.; Burke, David; Moalem‐Taylor, Gila; Howells, James
Abstract : Non‐invasive nerve excitability techniques have provided valuable insight into the understanding of neurological disorders. The widespread use of mice in translational research on peripheral nerve disorders and by pharmaceutical companies during drug development requires valid and reliable models that can be compared to humans. This study established a novel experimental protocol that enables comparative assessment of the excitability properties of motor and sensory axons at the same site in mouse caudal nerve, compared the mouse data to data for motor and sensory axons in human median nerve at the wrist, and constructed a mathematical model of the excitability of mouse axons. In a separate study, ischaemia was employed as an experimental manoeuvre to test the translational utility of this preparation. The patterns of mouse sensory and motor excitability were qualitatively similar to human studies under normal and ischaemic conditions. The most conspicuous differences between mouse and human studies were observed in the recovery cycle and the response to hyperpolarization. Modelling showed that an increase in temperature in mouse axons could account for most of the differences in the recovery cycle. The modelling also suggested a larger hyperpolarization‐activated conductance in mouse axons. The kinetics of this conductance appeared to be much slower raising the possibility that an additional or different hyperpolarization‐activated cyclic‐nucleotide gated (HCN) channel isoform underlies the accommodation to hyperpolarization in mouse axons. Given a possible difference in HCN isoforms, caution should be exercised in extrapolating from studies of mouse motor and sensory axons to human nerve disorders.